2013
DOI: 10.1007/s12275-013-2351-2
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of a mycovirus in Lentinula edodes

Abstract: A mycovirus was isolated from an edible mushroom, Lentinula edodes, that was suffering from a severe epidemic. Fractionation of the diseased cell extract by isopycnic centrifugation with 50% CsCl revealed that the diseased mushroom was infected by Lentinula edodes spherical virus (LeSV), a new spherical virus with a diameter of 55 nm. The particle of LeSV encapsidated the 12 kb RNA genome by a 120 kDa coat protein. BLAST analysis of the partially sequenced LeSV genome showed 95% sequence identity with a putati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
16
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…In some species, usually ascomycetes, there appear to be barriers to the transmission of viruses during sexual reproduction and the formation of sexual spores [27]. While no virus-transmission was observed via sexual spores in C. parasitica [31] and of the root rot pathogens Helicobasidium mompa and Rosellinia necatrix [32], wide-ranging rates of transmission were reported for H. annosum, [33], H. parviporum [21], and Lentinula edodes [34]. The lack of repetition of the experiment limit us to draw conclusions about the variance and reproducibility of our methodology and to estimate standard errors on the transmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…In some species, usually ascomycetes, there appear to be barriers to the transmission of viruses during sexual reproduction and the formation of sexual spores [27]. While no virus-transmission was observed via sexual spores in C. parasitica [31] and of the root rot pathogens Helicobasidium mompa and Rosellinia necatrix [32], wide-ranging rates of transmission were reported for H. annosum, [33], H. parviporum [21], and Lentinula edodes [34]. The lack of repetition of the experiment limit us to draw conclusions about the variance and reproducibility of our methodology and to estimate standard errors on the transmission rate.…”
Section: Discussionmentioning
confidence: 99%
“…The genomes of the three mycoviruses PgLV-1, LeMV, and LeSV comprise one large segment that encodes two putative proteins, but those vi- ruses appear to be capsidless based on previous reports (38,39,40). The RnMBV1 genome was previously reported to comprise two dsRNA segments (dsRNA1 and dsRNA2) (5).…”
Section: Discussionmentioning
confidence: 99%
“…It is plausible that these viruses may have an ancient origin and symbiosis maintenance in their respective hosts. Won et al [21] reported an encapsidated virus from L. edodes, whose partial genomic attribute has a high sequence similarity, up to 95 %, with that of the virus LeV-HKB. Additionally, N-terminal amino acid sequencing of the capsid protein (120 kDa) of the encapsidated virus (LeSV) identified some peptides that are located in the middle of the hypothetical protein encoded by HKB ORF1.…”
mentioning
confidence: 99%